Planificación estratégica institucional en el Gobierno Autónomo Descentralizado Parroquial Rural de Pimocha - Merello Chonillo, Eymi Carolina (2021)
This research was carried out in the Parish Autonomous Decentralized Government of Pimocha, which is responsible for executing works, programs, plans and social projects of public interest, among other actions, that guarantee the sustainable growth, development and well-being of the community. The objective of the case study was to analyze strategic planning, due to the fact that there are weaknesses in the planning processes, which conditions the fulfillment of their competences, cause the deterioration of the institutional image and causes disagreements in citizens because their requirements and needs are not met in a timely manner. The applied research methodology was descriptive and field type, in addition the inductive method was considered while the techniques were the interview and survey, supported by a questionnaire of questions, which were applied to the president and the human talent in charge of planning institutional and the citizens, in order to collect the necessary data to support this study. The results found were that the parish GAD has a weak strategic planning, which causes the lack of inputs, delays in processes and work stoppages, which affects the synergy of activities and conditions the fulfillment of the objectives. There are POA - PAC resolutions for the inclusion of projects not previously contemplated.